(untitled) (Research, Society and Development, 2021)
Autoimmune diseases are pathologies where the body itself develops an immune response against an autoantigen (autologous). There are several factors that trigger this loss of tolerance to the organism itself, such as genetic factors. The hereditary risk for most of these pathologies is attributable to multiple loci, the major contribution of which is made by the MHC genes. The objective of this research was to survey diagnosed cases of Autoimmune Diseases (DAIs) and Primary Immunodeficiencies (IP) in cities located in Agreste and in the capital of Pernambuco. In Agreste, four cities were selected for the development of this work. After the approval letter was released, and the ethics and research committee (CEP UNIFAVIP) approved, the research began. 1,000 medical records of patients diagnosed with these pathologies were analyzed between the years 2016 to 2018. Of these, only 94 medical records were used because they contain complete information for the results of this work. 93 records of DAIs and 1 IDP were identified. Even though it was not one of the objectives proposed, initially by the research, numerous difficulties were found both in access and in the interpretation of medical records, such as incomplete data and SID of the diagnosed disease. Celiac disease was the pathology that had the highest prevalence in the harsh Pernambuco.